PENGARUH PEMBELAJARAN LEARNING CYCLE TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI GAYA MAGNET - Anugrah, Rifki; Panjaitan, Regina Lichteria; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
Learning cycle makes student to have active role in learning process at class. While, science process skills demand student to have active role in having science experiment. Therefore, there is between learning cycle and science process skill. This research took the sample in particular from three classes were grouped into 3 group which are high, middle, and low (TSR), the determination on the test result knowledge of natural science (KAIPA). The three groups were given only one learning method, which is using Learning Cycle. Pre-experimental method was used with One-Group Pretest-Posttest Design. The result of research with significance level α = 0,05 indicates that Learning Cycle can improve student’s science process skills in group TSR. However, the difference test results of the three averages data gain group TSR shows the value of 0,331. In conclusion, there is no difference in the improvement of student’s science process skills in TSR Group.